EFFECTS of DIURON on MALE RAT REPRODUCTIVE ORGANS: A DEVELOPMENTAL and POSTNATAL STUDY - Fernandes, Glaura S. A.; Favareto, Ana Paula A.; Fernandez, Carla D. B. [UNESP]; Bellentani, Fernanda F. [UNESP]; Arena, Arielle C. [UNESP]; Grassi, Tony Fernando [UNESP]; Kempinas, Wilma G. [UNESP]; Barbisan, Luis Fernando [UNESP] (Taylor & Francis Inc, 2012)
This study was performed to determine whether developmental exposure (perinatal and juvenile) to the herbicide diuron exerted adverse effects on adult rat male reproductive system. Pregnant Sprague-Dawley rats received basal diet or diet containing diuron at 500 or 750 ppm from gestational day 12 (GD 12) until the end of lactation period (postnatal day 21, PND 21). After weaning male offspring received basal diet or diet containing diuron until PND 42 (peripubertal age). At PND 90, adult male rats from each experimental group were anesthetized and euthanized for evaluation of body and reproductive organ weights, sperm parameters, plasma testosterone levels, and testicular and epididymal histopathology. Male offspring exposed to diuron at 750 ppm displayed reduced body weight at PND 10, 21, 42, and 90 compared to controls. At PND 90, diuron treatment did not induce significant change in daily sperm production, sperm morphology and motility, and testosterone levels compared to controls. In conclusion, diuron at 750 ppm induced male offspring toxicity but these alterations were not permanent, as evidenced by absence of reproductive-system alterations in adult Sprague Dawley rats.